2019
DOI: 10.1037/cpp0000280
|View full text |Cite
|
Sign up to set email alerts
|

Improving support to siblings of children with cancer through a community-academic partnership.

Abstract: Siblings of children with cancer are a psychosocially at-risk group and have unmet needs that are typically not addressed within traditional hospital settings. The current study implemented a community-academic partnership model with SuperSibs-a nationwide, community-based, no-cost program for siblings of children with cancer, powered by Alex's Lemonade Stand Foundation-to evaluate and improve their sibling resources. Method: Researchers and Alex's Lemonade Stand Foundation staff partnered to plan and conduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…Furthermore, this study relied on parent accounts, because parents are often gatekeepers of sibling participation. Parent-identified support targets in the present study echoed previously documented sibling-reported desires for peer support, acknowledgment, involvement, and information (Oberoi et al, 2019; Patterson et al, 2011). However, because past research has described low parental awareness of siblings’ functioning in the context of pediatric cancer (Pariseau, Chevalier, Muriel, & Long, 2019), further exploration of the sibling perspective is necessary.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, this study relied on parent accounts, because parents are often gatekeepers of sibling participation. Parent-identified support targets in the present study echoed previously documented sibling-reported desires for peer support, acknowledgment, involvement, and information (Oberoi et al, 2019; Patterson et al, 2011). However, because past research has described low parental awareness of siblings’ functioning in the context of pediatric cancer (Pariseau, Chevalier, Muriel, & Long, 2019), further exploration of the sibling perspective is necessary.…”
Section: Discussionsupporting
confidence: 78%
“…Siblings of children with cancer want meaningful, age-appropriate, and consistently available support (Oberoi et al, 2019). Individual psychological and group-based interventions have been shown to improve sibling psychosocial well-being, medical knowledge, and perception of social support (Barrera et al, 2018; Prchal, Graf, Bergstraesser, & Landolt, 2012).…”
mentioning
confidence: 99%
“…22 (1) los niños sanos afirman que se sienten profundamente afectados por los sentimientos negativos de sus padres. De igual forma, es común que entre los niños sanos se generen sentimientos de ira, porque para ellos es normal estar enojados con la enfermedad y con todos los cambios que este diagnóstico causa en su vida [32][33][34][35][36]. Además, se genera enfado hacia sus padres, ya que los hermanos sienten que los padres no entienden la manera en la que se sienten, puesto que los padres creen que los niños con cáncer tienen una Calidad de Vida Relacionada en Salud (cvrs) menor que los hermanos sanos, cuando en realidad ambos tienen una calidad de vida baja [37,39].…”
Section: Cambio En Las Relaciones Parentalesunclassified
“…En otro estudio se identifica que algunos hermanos que asisten a campamentos de oncología informan que el apoyo social y la autoestima mejora después de la experiencia de pasar un tiempo de un campamento [32]. De acuerdo con una investigación, los hermanos explicaron la importancia de realizar sesiones psicoeducativas con información sobre el cáncer y utilizar simultáneamente juegos con ejercicios de yoga y respiración, ellos dicen que estas estrategias de afrontamiento son útiles inmediatamente después del diagnóstico, ya que permiten abordar simultáneamente las necesidades emocionales e informativas no satisfechas [33].…”
Section: Cambios Personalesunclassified
“…The SPARCCC team includes ALSF representatives and frequently collaborates with the organization. SPARCCC researchers and ALSF staff reviewed the existing literature on supporting siblings and conducted qualitative research to understand siblings’ perspectives of helpful resources, evaluate current SuperSibs resources, and identify potential new resources (Oberoi et al, 2019). Based on the findings, SuperSibs implemented changes including bolstering their school-based resources and revising their materials to incorporate new coping skills such as relaxation strategies.…”
Section: Application Of the Four-phase Model Of Transdisciplinary Res...mentioning
confidence: 99%